Urban management in Colombia gated communities: the case of Chia - Mendoza Jaramillo, Alejandro (Corporación Universitaria del Caribe, CECAR., 2015)
Abstract: This paper makes a brief tour of the logical planning and management processes around one of the most widespread phenomena occupation of land in Latin American cities –gated communities– landed in the town of Chia-Colombia. It is important to reveal the peculiarities and similarities in the real estate product installation and the urban management at the local government level in comparative perspective. The hypothesis underlying the research is that the urban management of gated communities began to fall significantly on the level of local government from administrative reforms occurred in 1990-2000 inflection, which generated a contradiction between a territorial phenomenon with metropolitan implications, which resulted in fragmentary legislation that sought to regulate gated communities and implement or legalize projects generated outside the existing regulatory framework. With respect to the methodological and instrumental proposal, a research is considered from a hypothetical-deductive perspective. It refers to a retrospective study of a phenomenon in a specific territory. A scenario in which the policy instruments are insufficient and inefficient to conduct a comprehensive urban management, which would prove that intensive gated location across the municipal territory is the product of property market exploitation, by the evidence of legal loopholes in addition to the successive reformulation of the instruments already in place to give them a legal basis. ___Keywords: gated communities, Chía, urban management. ___Resumen: El presente trabajo hace un breve recorrido por las lógicas y procesos de gestión urbanística en torno a uno de los fenómenos de ocupación del suelo más difundidos en las ciudades latinoamericanas - urbanizaciones cerradas -, aterrizado en el municipio de Chía-Colombia. Interesa develar las particularidades y similitudes en la instalación de ese producto inmobiliario y la gestión urbanística habida en el nivel local de gobierno en perspectiva comparativa. La hipótesis que fundamenta la investigación, es que la gestión urbanística de las urbanizaciones cerradas comenzó a recaer de manera importante sobre el nivel de gobierno local a partir de las reformas administrativas ocurridas en las reformas administrativas ocurridas en la inflexión 1990-2000, lo cual generó una contradicción entre un fenómeno territorial con implicancias metropolitanas, los cuales resultaron en normativas fragmentarias que buscaron regular las urbanizaciones cerradas y viabilizar o legalizar los emprendimientos generados fuera del marco normativo vigente. La propuesta metodológica e instrumental, se considera la investigación desde una perspectiva hipotético-deductiva. Se remite a un estudio retrospectivo de un fenómeno en un territorio específico. Se evidencia un panorama en el que lo instrumentos normativos resultan insuficientes e ineficientes para llevar a cabo una gestión urbanística integral, lo que comprobaría que la localización intensiva de urbanizaciones cerradas a lo largo y ancho del territorio municipal, es producto del aprovechamiento por parte del mercado inmobiliario de los vacíos legales existentes además de la sucesiva reformulación de los instrumentos ya vigentes para darles un sustento legal. ___Palabras clave: urbanizaciones cerradas, Chía, gestión urbanística. ___Recibido: 19 de julio de 2015. Aceptado: 15 de septiembre de 2015.